High-Performance Dual-View 3-D Display System Based on Integral Imaging - Yan Xing; Qiong-Hua Wang; Ling Luo; Hui Ren; Huan Deng (IEEE Photonics Journal, 2019)
In this paper, a dual-view three-dimensional (3-D) display is reported to provide two different high-quality 3-D images in different viewing zones simultaneously. By introducing an improved integral imaging system, which consists of a display panel, a large-pitch lens array, and a directional diffuser screen, two different 3-D images can be reconstructed in different wide viewing zones with high 3-D resolution. In addition, a high accurate pickup method based on projective transformation is presented. A prototype of the proposed dual-view 3-D display is developed and it has good performance.